2020
DOI: 10.3389/fnins.2020.00091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TRPV1 Activation by Capsaicin and Endogenous N-Arachidonoyl Taurine on Synaptic Transmission in the Prefrontal Cortex

Abstract: While the transient receptor potential vanilloid 1 (TRPV1) ion channel, a non-selective calcium-permeable cation channel with high Ca 2+ permeability, mainly integrates physical and chemical stimuli for nociception, recent studies suggest that it has a role beyond a noxious thermal sensor. In fact, TRPV1 is presently being considered as a target for treating pathophysiological processes including pain, fear, and anxiety disorders. Although this ion channel has many potential roles, its underlying mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Recently, the presence of TRPV1 in the soma of pyramidal neurons of the prelimbic cortex of the prefrontal cortex (PFC) has been reported [85]. This finding is interesting since the activation of TRPV1 produces an increase in the frequency of spontaneous excitatory postsynaptic currents (sEPSC) in the substantia gelatinosa of the rat spinal cord and in the substantia nigra [86,87].…”
Section: N-acyl Amino Acids/neurotransmittersmentioning
confidence: 94%
“…Recently, the presence of TRPV1 in the soma of pyramidal neurons of the prelimbic cortex of the prefrontal cortex (PFC) has been reported [85]. This finding is interesting since the activation of TRPV1 produces an increase in the frequency of spontaneous excitatory postsynaptic currents (sEPSC) in the substantia gelatinosa of the rat spinal cord and in the substantia nigra [86,87].…”
Section: N-acyl Amino Acids/neurotransmittersmentioning
confidence: 94%
“…However, it is known that AEA is a partial agonist for CB 1 R [ 120 ] and it has been widely demonstrated that activation of CB 1 R reduces rather than facilitates GABAergic synaptic activity [ 98 , 99 ]. Similarly, AEA can activate transient receptor potential vanilloid type 1 (TRPV1) receptors [ 121 , 122 , 123 ], that also have been shown to decrease GABAergic neurotransmission in the mPFC of mice [ 124 ]. Noteworthy, as demonstrated in the present study, structurally related lipids to AEA, including PEA, OEA, and NAGly, which do not activate cannabinoid receptors, are often altered in parallel with changes in AEA [ 125 , 126 , 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAT reduces ACSL4, LPCAT3 and PLTP, which are all essential for AA incorporation into the plasma membrane [40,41]. Of note, NAT activates transient receptor potential vanilloid 1 (TRPV1) channel and Ca 2+ [47]; however, whether NAT suppresses the three enzymes via one common mechanism, such as TRPV1 and Ca 2+ , is unclear and worth investigating in the future.…”
Section: Discussionmentioning
confidence: 99%